Obesity and Subtypes of Incident Cardiovascular Disease. Issue 8 (28th July 2016) - Ndumele, Chiadi E.; Matsushita, Kunihiro; Lazo, Mariana; Bello, Natalie; Blumenthal, Roger S.; Gerstenblith, Gary; Nambi, Vijay; Ballantyne, Christie M.; Solomon, Scott D.; Selvin, Elizabeth; Folsom, Aaron R.; Coresh, Josef
Abstract : Background: Obesity is a risk factor for various subtypes of cardiovascular disease (CVD), including coronary heart disease (CHD), heart failure (HF), and stroke. Nevertheless, there are limited comparisons of the associations of obesity with each of these CVD subtypes, particularly regarding the extent to which they are unexplained by traditional CVD mediators. Methods and Results: We followed 13 730 participants in the Atherosclerosis Risk in Communities (ARIC) study who had a body mass index ≥18.5 and no CVD at baseline (visit 1, 1987–1989). We compared the association of higher body mass index with incident HF, CHD, and stroke before and after adjusting for traditional CVD mediators (including systolic blood pressure, diabetes mellitus, and lipid measures). Over a median follow‐up of 23 years, there were 2235 HF events, 1653 CHD events, and 986 strokes. After adjustment for demographics, smoking, physical activity, and alcohol intake, higher body mass index had the strongest association with incident HF among CVD subtypes, with hazard ratios for severe obesity (body mass index ≥35 versus normal weight) of 3.74 (95% CI 3.24–4.31) for HF, 2.00 (95% CI 1.67–2.40) for CHD, and 1.75 (95% CI 1.40–2.20) for stroke ( P <0.0001 for comparisons of HF versus CHD or stroke). Further adjustment for traditional mediators fully explained the association of higher body mass index with CHD and stroke but not with HF (hazard ratio 2.27, 95% CI 1.94–2.64). Conclusions: The link between obesity and HF was stronger than those for other CVD subtypes and was uniquely unexplained by traditional risk factors. Weight management is likely critical for optimal HF prevention, and nontraditional pathways linking obesity to HF need to be elucidated.